New species of Scapheremaeus (Acari: Oribatida: Cymbaeremaeidae) from an epiphytic environment in Morelos, Mexico - Palacios-Vargas, José G.; Murillo, Kevin A. Jaimes; Ojeda, Margarita (Zootaxa, 2024)
Scapheremaeus subiasi sp. nov. from El Zapote, Morelos is described and illustrated. It is morphologically similar to other Mexican species living in moss and lichens, i.e. S. magdalenae and S. hectorperezius, in sharing the presence of a humeral process, body ornamentation, number of notogastral setae (10) and being monodactylous. Main differences include body size, well developed lamellar tubercles and general appearance of the posterior end of notogaster. In addition, an identification key for all known Mexican species in the genus is given.